Evaluation of Three Rapid Diagnostic Methods for Direct Identification of Microorganisms in Positive Blood Cultures - Martinez, Raquel M. (American Society for Microbiology, 2014)
The identification of organisms from positive blood cultures generally takes several days. However, recently developed rapid diagnostic methods offer the potential for organism identification within only a few hours of blood culture positivity. In this study, we evaluated the performance of three commercial methods to rapidly identify organisms directly from positive blood cultures: QuickFISH (AdvanDx, Wolburn, MA), Verigene Gram-Positive Blood Culture (BC-GP; Nanosphere, Northbrook, IL), and matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) with Sepsityper processing (Bruker Daltonics, Billerica, MA). A total of 159 blood cultures (VersaTREK Trek Diagnostic Systems, Cleveland, OH) positive for Gram-positive and Gram-negative bacteria as well as yeast were analyzed with QuickFISH and MALDI-TOF MS. In all, 102 blood cultures were analyzed using the BC-GP assay. For monomicrobial cultures, we observed 98.0% concordance with routine methods for both QuickFISH (143/146) and the BC-GP assay (93/95). MALDI-TOF MS demonstrated 80.1% (117/146) and 87.7% (128/146) concordance with routine methods to the genus and species levels, respectively. None of the methods tested were capable of consistently identifying polymicrobial cultures in their entirety or reliably differentiating Streptococcus pneumoniae from viridans streptococci. Nevertheless, the methods evaluated in this study are convenient and accurate for the most commonly encountered pathogens and have the potential to dramatically reduce turnaround time for the provision of results to the treating physician.